Il dolore, tra medicina, diritto e machine learning. Potenziali euristici delle neuroscienze affettive fondamentali, da Sequeri a Panksepp - Heritier, Paolo; Caldo, Davide (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2021)
The paper outlines a theoretical framework to implement pain analysis through predictive tools inspired by the neuroscientific work of Apkarian, Damasio, Panksepp. It then identifies a paradigm of ‘affective turn’ able to dialogue with legal and anthropological thinking, starting from Sequeri, and Vico’s New Science, in order to configure a notion of normative affective-fundamental neuroscience: with the aim of overcome the myths of behaviorism and cognitivism in psychology, and positivism and realism in philosophy of law.